A Randomized, Controlled Safety, and Immunogenicity Trial of the M72/AS01 Candidate Tuberculosis Vaccine in HIV-Positive Indian Adults. Issue 3 (January 2016) - Kumarasamy, Nagalingeswaran; Poongulali, Selvamuthu; Bollaerts, Anne; Moris, Philippe; Beulah, Faith Esther; Ayuk, Leo Njock; Demoitié, Marie-Ange; Jongert, Erik; Ofori-Anyinam, Opokua
Abstract : Abstract: Human immunodeficiency virus (HIV)-associated tuberculosis is a major public health threat. We evaluated the safety and immunogenicity of the candidate tuberculosis vaccine M72/AS01 in HIV-positive and HIV-negative Indian adults. Randomized, controlled observer-blind trial (NCT01262976). We assigned 240 adults (1:1:1) to antiretroviral therapy (ART)-stable, ART-naive, or HIV-negative cohorts. Cohorts were randomized 1:1 to receive M72/AS01 or placebo following a 0, 1-month schedule and followed for 12 months (time-point M13). HIV-specific and laboratory safety parameters, adverse events (AEs), and M72-specific T-cell-mediated and humoral responses were evaluated. Subjects were predominantly QuantiFERON-negative (60%) and Bacille Calmette–Guérin-vaccinated (73%). Seventy ART-stable, 73 ART-naive, and 60 HIV-negative subjects completed year 1. No vaccine-related serious AEs or ART-regimen adjustments, or clinically relevant effects on laboratory parameters, HIV-1 viral loads or CD4 counts were recorded. Two ART-naive vaccinees died of vaccine-unrelated diseases. M72/AS01 induced polyfunctional M72-specific CD4 + T-cell responses (median [interquartile range] at 7 days postdose 2: ART-stable, 0.9% [0.7–1.5]; ART-naive, 0.5% [0.2–1.0]; and HIV-negative, 0.6% [0.4–1.1]), persisting at M13 (0.4% [0.2–0.5], 0.09% [0.04–0.2], and 0.1% [0.09–0.2], respectively). Median responses were higher in the ART-stable cohort versus ART-naive cohort from day 30 onwards ( P ⩽ 0.015). Among HIV-positive subjects (irrespective of ART-status), median responses were higher in QuantiFERON-positive versus QuantiFERON-negative subjects up to day 30 ( P ⩽ 0.040), but comparable thereafter. Cytokine-expression profiles were comparable between cohorts after dose 2. At M13, M72-specific IgG responses were higher in ART-stable and HIV-negative vaccinees versus ART-naive vaccinees ( P ⩽ 0.001). M72/AS01 was well-tolerated and immunogenic in this population of ART-stable and ART-naive HIV-positive adults and HIV-negative adults, supporting further clinical evaluation. Abstract : Supplemental Digital Content is available in the text